Epiphytic metazoans on emergent macrophytes in oxbow lakes of the Krapina River, Croatia: differences related to plant species and limnological conditions - Spoljar, Marija; Fressl, Jelena; Drazina, Tvrtko; Meseljevic, Matija; Grcic, Zlatko (Acta Botanica Croatica, 2012)
This study investigated the structure of the epiphytic metazoans on emerged macrophytes in the littoral zone of two oxbow lakes with different trophic levels. Differences in the diversity and density of the epiphytic metazoans were analyzed in relation to plant architecture(simple or complex stems), food resources (algae and detritus) and water characteristics (transparency and derived trophic state index). Asignificant negative correlation was found between detritus on plants as food resource, and diversity and density of epiphytic metazoans, indicating grazing of microphagous species. Rotifers dominated in diversity and density in the epiphyton on all habitats. Total density of metazoans, rotifers and copepods in epiphyton were significantly higher on Mentha in mesotrophic lake than on Iris in a eutrophic lake.We presume that macrophyte belt width and trophic state governed biotic interactions and consequently epiphytic assemblages more strongly than macrophyte architecture. However, a Mentha habitat showed a slightly higher density and diversity of epiphytic metazoans in relation to Iris at the same site, but these differences were not significant.